“Faster, Higher, Stronger – Together”?: the Crisis of the World Sports Movement in the Context of the Pandemic and the Problem of Racism - E. V. Khakhalkina; A. V. Munko (Vestnik MGIMO-Universiteta)
In recent years, sport reflects the most painful trends in social development, economics, culture, and international politics.Major international sporting events of the summer 2021 reveal, according to authors, the crisis of Olympism and degradation of the ideological and philosophical basis of professional sport, which is an important element of international relations undergoing a noticeable transformation under the influence of the coronavirus pandemic and the exacerbation of racist traumas of the past.The study is based on social constructivism, it uses elements of critical discourse analysis and comparative analysis. European Football Championship and Olympic Games in Tokyo 2021, FIFA 2022 qualifiers show some politically motivated refereeing, as well as bursts of racism on the part of individual participants. The principle of “political correctness” widespread in the West makes it difficult to discuss and deal with historical and colonial traumas, as well as with the crisis in the values of “fair play” in professional sports, caused by its commercialization and politicization.The article concludes that the observed facts stem, among other things, from the revival of the Black Lives Matter movement in the spring of 2020, which spread beyond the borders of the United States, the formation and expansion of the “cancel culture”, as well as the growing influence of social networks and media on world public opinion. The coronavirus pandemic, announced in the spring of 2020, has exacerbated old national problems, and brought to the fore new phenomena in world sports.